Case Report: Diffuse pulmonary lymphangiomatosis in a child - Zhang, Ya-nan; Yuan, Zhen; Du, Jin-chen; Liu, Bin; Li, Fu; Hu, Shou-Cai; Li, Qing-Xin (Frontiers in Pediatrics, 2026)
We report a rare case of generalized lymphatic anomaly (GLA) in a 12-year-old male, presenting with intermittent cough, expectoration, and hemoptysis exacerbated by strenuous activity. Key features included bilateral pleural/pericardial effusions; chest/abdominal CT showed diffuse mediastinal infiltration, bronchovascular/interlobular septal thickening, and extrathoracic extension to periaortic abdominal tissues. Definitive diagnosis was confirmed by thoracoscopic biopsy and immunohistochemistry (CD31+, D2-40+, Ki-67 ≈ 3%), differentiating it from mimics like pulmonary lymphangiectasia. The patient achieved symptomatic remission after pericardiectomy, thoracic catheter drainage, and postoperative sirolimus. This case enriches pediatric GLA literature, highlights multidisciplinary diagnosis value, and supports mTOR inhibitors’ role in pediatric GLA management.